A Theology of the Old Testament: Cultural Memory, Communication and Being Human. By J. W. Rogerson - Moberly, Walter (The journal of theological studies, 2010)
Volumes entitled ‘Theology of the Old Testament’, or something similar, tend to run along certain generally predictable, albeit various, lines. This one does not. It is perhaps the freshest, most distinctive contribution to the genre that I have read. I never knew where Rogerson would go next. But as the writing is unfailingly lucid and judicious, and the engagement with the text of the Old Testament and with contemporary issues is searching, I found it a remarkably absorbing and instructive read., Rogerson’s approach is, in essence, simple. He does not wish to offer an account of religious thought in the ancient world.